Education keypad / Muhammad Hafidz Ahmad Mortza, Muhammad Dzain Aiman Muhammad Zainuddin and Mohamad Nor Afiq Mohd Ramli - Ahmad Mortza, Muhammad Hafidz; Muhammad Zainuddin, Muhammad Dzain Aiman; Mohd Ramli, Mohamad Nor Afiq (2015)
Nowadays, education is becoming the most important resource in our daily life. Almost every single person needs education to survive in this modem society. Without a proper education, a person might be left behind and looked down by the society. Children are the next generation that needs to carry our education to the next generation. So the first steps that must take to ensure the next generation is well educated are to make sure our children get a well education. Children nowadays are not attracted to reading books but more attracted to devices. Solution can solve this problem by making a device that can be used by children and slow learners to attract them towards education. First of all, this project is a low cost budget and easy to make. This project represents a method how to improve knowledge among children and slow learners. The flow of the project can be cooperating with the main component that is PIC16F887. This component act as a mastermind to make sure this circuit can